Goldie Roth unchained: risk and its management in Lian Tanner’s Museum of Thieves - Danielle Wood (Barnboken: Tidskrift för Barnlitteraturforskning, 2014)
In her children’s action adventure novel Museum of Thieves, Lian Tanner overtly critiques adult risk-aversion and the over-protection of children. The protagonist is Goldie, an unruly child who escapes the oppressive regime of the City of Jewel where children up to the age of 12 are chained, for their own safety, to adult companions. Goldie escapes Jewel’s power structures and enters a mysterious museum housing the city’s unwanted wildness and danger. In its opening chapter Museum of Thieves establishes a subversive schema that problematises concepts of safety and order and glorifies chaos and risk, but this paper argues that as the novel progresses the author finds the schema increasingly difficult to control. It is tempting to read the museum as a “time out” zone such as CS Lewis’s Narnia, L Frank Baum’s Oz, and Maurice Sendak’s “place where the wild things are”: a space in which child characters can gain self-knowledge and skills before returning to an adult-dominated order. However, because of the degree to which Jewel and its structures are pathologised, Tanner finds she cannot bring Goldie back from “time out”. But rather than being a transgressive text, Museum of Thieves ends in a much less subversive place than it sets out to reach; the museum is revealed as a tightly controlled space and Goldie is well-protected, both within the diegesis by the museum’s special features, and beyond the diegesis by the author and the author’s cognisance of contemporary publishing industry expectations about the depiction of risk in children’s fiction.